PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA VIDEO ANIMASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII SMP NEGERI 1 KUPANG TIMUR - Yulius Mata’a; Andam S. Ardan; Arini Rahma Dhani (SINERGI : Jurnal Riset Ilmiah, 2026)
Improving the quality of education requires the support of effective learning strategies, including appropriate learning models, instructional media, adequate learning facilities, and competent educators. One learning strategy that can be implemented is the Problem-Based Learning (PBL) model assisted by animated video media. The PBL model encourages students to actively participate in the learning process, while animated videos enhance students' interest and engagement during instruction. As a result, students' critical thinking skills improve, enabling them to achieve optimal learning outcomes.Based on previous research, the implementation of the PBL model was found to be less effective because many students were still engaged in unrelated activities, excessive discussions, and paid insufficient attention to the teacher's explanations during the learning process. Consequently, their learning outcomes were not optimal. Therefore, this study aimed to investigate the implementation of the Problem-Based Learning model assisted by animated video media to improve the learning outcomes of Grade VIII G students at SMP Negeri 1 Kupang Timur. This study employed Classroom Action Research (CAR), which was conducted in two cycles.The findings indicated an improvement in student learning activities, with the average activity score increasing from 67.85% in Cycle I to 73.21% in Cycle II. Furthermore, the use of animated video media within the syntax of the PBL model proved effective in simplifying abstract biological concepts into more concrete representations. This approach successfully captured students' attention, enhanced their motivation and participation in group activities, and contributed to improved student learning outcomes